Metabolic Outcomes of Changing From Rilpivirine/Tenofovir Disoproxil Fumarate/Emtricitabine to Rilpivirine/Tenofovir Alafenamide/Emtricitabine: A Longitudinal Study - Ping‐Feng Wu; Hsi‐Hsun Lin; Hsin‐Pai Chen; Po‐Chieh Huang; Meng‐Yu Ke (Health Science Reports)
ABSTRACT Background and Aims People living with human immunodeficiency virus (HIV, PLWH) are aging, and there are growing concerns regarding combined antiretroviral therapy (cART)‐associated negative metabolic consequences. We aimed to investigate the metabolic outcomes of PLWH by replacing rilpivirine (RPV)/tenofovir disoproxil fumarate (TDF)/emtricitabine (FTC) with RPV/tenofovir alafenamide (TAF)/FTC. Methods This retrospective study enrolled PLWH who changed from RPV/TDF/FTC to RPV/TAF/FTC between January 2019 and September 2023. Metabolic profiles were compared 1 year before and 3 years after changing cART using Cochran's Q and one‐way ANOVA. The independent risk factors for metabolic syndrome were analyzed using logistic regression. Results A total of 182 patients were enrolled. The prevalence of metabolic syndrome has increased from 28% to 40.7%. The prevalence of hypertension and abnormal lipid levels significantly increased in the first year after changing cART, but the prescription of medicine for dyslipidemia increased in the second year (p = 0.025) and that for hypertension increased in the third year (p < 0.001). In addition to the criteria, body mass index (BMI) before changing cART was the only predictor of metabolic syndrome in the third year (OR 1.36; 95% CI 1.19–1.55; p < 0.001). The prevalence of metabolic syndrome and BMI did not increase significantly during the second and third years. Conclusions A gradually higher prevalence of metabolic syndrome among PLWH occurred with changes from RPV/TDF/FTC to RPV/TAF/FTC but plateaued beyond 2 years. However, fewer drugs for dyslipidemia, diabetes, and hypertension were prescribed within the first year after changing cART.